2006
DOI: 10.1044/1058-0360(2006/030)
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Communicative Participation: A Review of Self-Report Instruments in Speech-Language Pathology

Abstract: Purpose-To assess the adequacy of self-report instruments in speech-language pathology for measuring a construct called communicative participation.Method-Six instruments were evaluated relative to (a) the construct measured, (b) the relevance of individual items to communicative participation, and (c) their psychometric properties.Results-No instrument exclusively measured communicative participation. Twenty-six percent (n = 34) of all items (N = 132) across the reviewed instruments were consistent with commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
164
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 208 publications
(171 citation statements)
references
References 37 publications
2
164
0
5
Order By: Relevance
“…However, in line with international consensus, there were felt to be few reliable measures to assess children's performance, that is, functional use of speech and language in their everyday context rather than 'capacity' under controlled or 'ideal' test conditions. 297 Of particular note was the lack of common valid and reliable tools to specifically identify the need for intervention in PSLI for the themes of 'adult understanding', 'adult-child interaction' and, to a lesser degree, 'generalisation' and 'functional use of language'.…”
mentioning
confidence: 99%
“…However, in line with international consensus, there were felt to be few reliable measures to assess children's performance, that is, functional use of speech and language in their everyday context rather than 'capacity' under controlled or 'ideal' test conditions. 297 Of particular note was the lack of common valid and reliable tools to specifically identify the need for intervention in PSLI for the themes of 'adult understanding', 'adult-child interaction' and, to a lesser degree, 'generalisation' and 'functional use of language'.…”
mentioning
confidence: 99%
“…The insider perspective is essential in order to obtain meaningful information about the experience of health conditions, and also the consequences in terms of participation. Only the afflicted individual himself/herself can have an informed opinion about his/her own feelings, needs, and habits when it comes to speech and communication [16]. Proxy measures, that is, information obtained by an outside observer, have also been found to be rather unreliable, for example, regarding ratings of speech usage.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews of language assessment tools from an ICF perspective revealed that only the single domain of Body Functions and Structures [28,37] is well covered. Notably 'communication participation' in real-life situations is not represented [37,38]. Thus, functioning is not well assessed by most contemporary assessment tools.…”
Section: The Icf-cy Framework and Social Communicationmentioning
confidence: 99%